2019
DOI: 10.1016/j.jjcc.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between maintenance of sinus rhythm and clinical outcomes in patients with heart failure with preserved ejection fraction and atrial fibrillation

Abstract: Background: Although atrial fibrillation (AF) is associated with exacerbation of heart failure with preserved ejection fraction (HFpEF), the relationships between maintenance of sinus rhythm (SR) and clinical outcomes in HFpEF is unknown. We investigated whether maintenance of SR was associated with better prognosis compared with rate control in patients with concomitant HFpEF and AF. Methods: We conducted a retrospective, observational study of 283 patients with HFpEF and AF. Of these, 107 patients achieved m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 32 publications
(44 reference statements)
5
50
1
Order By: Relevance
“…The beneficial effect of rhythm control with anti-arrhythmic drugs in HF was limited because of their low efficacy of maintenance of sinus rhythm and toxicities. In the present study [10], the rates of sinus rhythm maintenance were relatively high (72.2%) in the rhythm control group. A recent meta-analysis showed that AF catheter ablation can improve left ventricular EF, and reduce allcause mortality, and HF hospitalizations in HFrEF patients with AF [7].…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…The beneficial effect of rhythm control with anti-arrhythmic drugs in HF was limited because of their low efficacy of maintenance of sinus rhythm and toxicities. In the present study [10], the rates of sinus rhythm maintenance were relatively high (72.2%) in the rhythm control group. A recent meta-analysis showed that AF catheter ablation can improve left ventricular EF, and reduce allcause mortality, and HF hospitalizations in HFrEF patients with AF [7].…”
contrasting
confidence: 40%
“…In this issue of the Journal of Cardiology, a retrospective, observational, multicenter study utilizing data from 11 participating institutions was demonstrated to investigate the efficacy and safety of rhythm control therapy mainly by catheter ablation in 283 Japanese HFpEF patients with AF [10]. The authors used a propensity score matched cohort consisting of 79 patients with rhythm control therapy and 79 patients with rate control therapy.…”
mentioning
confidence: 99%
“…CASTLE‐AF showed the efficacy of rhythm control by AF ablation in patients with HFrEF 10 . Recently, Machino‐Ohtsuka et al 15 reported that maintenance of sinus rhythm was associated with a lower risk of HF hospitalization in patients with HFpEF and AF. Therefore, therapeutic strategies to maintain sinus rhythm are indicated to reduce HFpEF hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In another retrospective analysis, Black‐Maier et al 6 concluded that procedure success rate and functional improvement after AF ablation were similar in HFrEF and HFpEF. More recently, a propensity‐matched cohort study showed that rhythm control in AF‐HFpEF via either ablation or medication led to a significantly reduced composite of cardiovascular death and HF hospitalization compared with rate control 7 . Nonetheless, despite early promising results, there has been concern that AF ablation in AF‐HFpEF may carry a lower success rate and a potentially higher risk of procedural complications due to more complex atrial remodeling and higher comorbidity burden.…”
mentioning
confidence: 99%
“…2 Furthermore, AF-HFpEF patients are known to have a worse prognosis compared with HFpEF patients without AF, 3 More recently, a propensity-matched cohort study showed that rhythm control in AF-HFpEF via either ablation or medication led to a significantly reduced composite of cardiovascular death and HF hospitalization compared with rate control. 7 Nonetheless, despite early promising results, there has been concern that AF ablation in AF-HFpEF may carry a lower success rate and a potentially higher focal ablation for atrial tachycardia/nonpulmonary vein focus, superior vena cava ablation, and cavotricuspid isthmus linear ablation at the discretion of the operators. 8 The primary outcome was rehospitalization due to HF.…”
mentioning
confidence: 99%